INOVASI PRODUK, WORD OF MOUTH (WOM) DAN KEWAJARAN HARGA: KUNCI PENGARUH TERHADAP KEPUTUSAN PEMBELIAN DI GARMENT GIRI COLLECTION - I Komang Rai Putra Yasa; Daniel Manek (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
The business world continues to experience increasingly rapid growth and change each year. This led to a surge in new businesses across various categories, both goods and services, to meet the needs of the community. One of the needs that cannot be separated from life is clothing. Business owners compete to meet the needs and desires of consumers, from selecting good materials to the manufacturing process, with the aim of creating a product of the highest quality. This research aims to determine the influence of product innovation, word of mouth (WOM), and price fairness on purchasing decisions. The research method used is quantitative. The population consists of consumers at Garment Giri Collection, with a sample size of 70 people. The data analysis techniques used were Validity Test, Reliability Test, Descriptive Test, Multiple Linear Regression Analysis, Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroskedasticity Test, F Test, T Test, and R2 Test. The research results showed that product innovation had a positive and significant effect on purchasing decisions, word of mouth had a positive and significant effect on purchasing decisions, and price fairness had a positive and significant effect on purchasing decisions. The advice that can be given to the researcher is that Garment Giri Collection should follow consumer fashion trends, especially among teenagers. It is hoped that the company will improve the shortcomings of its products, minimize negative experiences consumers have with its products, and adjust its product prices to compete with other garment businesses.